Bonding and vibrations of CHxO and CHx species (x=1–3) on a palladium nanoparticle representing model catalysts - Kozlov, Sergey M. (2011)
This computational study deals with the adsorption of CH3, CH2, CH, CH2OH, CH3O, CH2O and CHO species on a nanoparticle Pd79 that mimics experimentally investigated model Pd catalysts. We quantify structural, energetic and vibrational parameters of these adsorption complexes and analyse their dependence on the adsorption site. Most of the considered low coordinated adsorption sites are found to be favoured by 20–50 kJ/mol over the sites on (1 1 1) facets. Some of the studied species have distinguishable vibrational parameters at different adsorption sites of the model nanoparticle, making possible spectroscopic characterization of respective adsorption complexes.